1991
DOI: 10.1177/00220345910700050501
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Local Interfacial Geometry on the Measurement of the Tensile Bond Strength to Dentin

Abstract: The local detail of the geometry of the adhesive interface can have a significant effect on the measurement of dentin bond strengths and may be a contributory factor in the discrepancies among data in the published literature. The potential effect on the dentin bond strength due to modifications of the local stress distribution at the adhesive/dentin interface has been assessed. Tensile bond strength measurements for specimens with and without an adhesive flash were carried out and compared with the stress dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
94
0
23

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(134 citation statements)
references
References 4 publications
6
94
0
23
Order By: Relevance
“…Along with the improvement in bond strength of the current generation dentin bonding agents, cohesive failure in dentin during shear bond strength tests was observed more frequently 14) . However, rather than improvement in the material properties, the test mechanics of the shear test set-up, such as loading condition [15][16][17] and small changes in the geometric arrange- 18,19) , was suggested to cause the variations in strength values and cohesive fracture in dentin.…”
Section: โ…ณ Discussionmentioning
confidence: 99%
“…Along with the improvement in bond strength of the current generation dentin bonding agents, cohesive failure in dentin during shear bond strength tests was observed more frequently 14) . However, rather than improvement in the material properties, the test mechanics of the shear test set-up, such as loading condition [15][16][17] and small changes in the geometric arrange- 18,19) , was suggested to cause the variations in strength values and cohesive fracture in dentin.…”
Section: โ…ณ Discussionmentioning
confidence: 99%
“…This might be due to the fact that the bonding agents were coated on the entire dentin area. Van Noort et al 13) had reported a two fold increase in shear bond strengths when coating the entire dentin area over those measured on a constrained area. Thus, in the iris method, the area must be measured after debonding and the shear bond strength should be calculated by dividing the maximum applied force by the measured area.…”
Section: โ…ณ Discussionmentioning
confidence: 99%
“…Finite element analysis has been used to describe the distribution of interfacial shear stresses 5,8,9,13) . From these it appears that the interfacial shear stresses are highly non-uniform and strongly influenced by bonding geometry, loading conditions and the mismatch in elasticity among the bonded layers.…”
Section: โ…ณ Discussionmentioning
confidence: 99%
“…It should be mentioned that a gradation exists in both morphology and mechanical properties from the dentin-enamel junction to the outer layer of enamel. When doing mechanical tests, such as the tensile strength test, stress distributions may be strongly influenced by factors such as loading characteristics and specimen size 14) . Thus, one must expect uneven stress distributions and acknowledge that the mechanical values reported are nominal values which require cautious interpretation.…”
Section: Introductionmentioning
confidence: 99%